Financial performance in Islamic banking and Shari’ah supervision under interventionist regulatory approach: a system-GMM dynamic panel analysis - Nomran, Naji Mansour; Haron, Razali (Research Center for Islamic Economics, 2020)
The relationship between Shari’ah supervision and Islamic banks’ (IBs) performance is still ambiguous particularly for banks across countries that have different regulatory environments. Pakistan adopts an interventionist regulatory approach which is exclusive to Shari’ah governance (SG) system in Pakistan. This approach differ from the other adopted approaches in countries that have either high or low degree of regulatory interference. Thus, this study examines how Shari’ah supervision mechanism, as represented by the Shari’ah supervisory board, and its characteristics, can influence the performance of IBs in Pakistan. The sample comprises 67 Islamic bank year observations for the period from 2007 to 2015. The performance-governance relationship is estimated using a range of econometric techniques including the dynamic system-GMM estimator. The results reveal modest support for a positive association between Shari’ah supervision and performance. The study concludes that SG practices in the Pakistani IBs still suffer from some drawbacks which require more improvements by the respective regulators. Most of these drawbacks are related to the SG regulatory frameworks which are related to the SSBs’ roles and characteristics.